(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the contributions of social media platforms to political empowerment of youth in Opobo/Nkoro Local Government Area, Rivers State. The study was guided by four research questions. The descriptive survey research design was used for the study. The population of the study comprised 964 youths from seven registered youth organizations in Opobo/Nkoro Local Government Area. The simple random sampling technique by balloting was used to sample 241 youths. Instrument for data collection was a questionnaire titled Contributions of Social Media Platforms to Political Empowerment of Youth Questionnaire (CSMPPEYQ). The instrument was face validated by three experts. The reliability coefficient values of 0.82, 0.84, 0.77 and 0.71 were generated for clusters A, B, C, and D. The data were analyzed using mean and standard deviation. Findings of the study revealed that the extent the use of Instagram can contribute to political participation of youth in Opobo/Nkoro Local Government Area was high; the extent to which the use of Facebook can contribute to freedom of expression of youth was high. Based on the findings, some recommendations were made, among which was that: community leaders and the government should collaborate to develop and implement community programmes that will help to educate youth about responsible and ethical use of Instagram. Educational institutions should incorporate Facebook platforms as tools for enhancing political education among the youths.